USING DEBATES TO IMPROVE SPEAKING SKILLS - Muminova Anarkhan Abdilazizovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: Debates occupy a vital role in nurturing individuals to become active, initiative, and critical thinkers. In the course of debates, every participant’s word, method of expression, the logical sequence, and fluency are put to the test. Debates serve as a preparatory stage for students, enabling them to justify their opinions, analyze opposing viewpoints, and either refute or defend them by providing arguments and reinforcing their convictions. Participation in debates compels one to focus on their spoken language, maximizing their ability to use the language effectively. This, in turn, develops high-level communication skills, teaching one to present their ideas systematically, maintain composure, and speak confidently in the presence of others.